STUDY OF POSSIBILITIES OF USING WOOD ASH - Ratnika, Līga; Laizāne, Ināra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Within the framework of the work, the chemical properties of 32 samples from 3 different heat energy production sources were determined in order to evaluate the possibilities of their use. Possibilities of using wood ash in agriculture, forestry and construction were considered. Ash samples contain high concentrations of calcium and its compounds. The prospect of using ash is to use it to fertilize agricultural and forest land.